RENEWABLE ENERGY, AN INFLUENTIAL FACTOR IN THE DEVELOPMENT OF THE DANUBE TRANSPORT CORRIDORS ROMANIA - BULGARIA AND A SUPPORT MECHANISM IN INTERMODAL CONNECTIONS - Cristiana SÎRBU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aims to present the need and the importance of using efficiently the energy and finding new ways to improve the transport based on renewable energy. The paper is based on a large number of official information sources which are structured and presented in the author's opinion. The main results emphasize that the Danube region is a large river basin and ecological corridor requiring a regional approach to nature conservation, spatial planning and water management. The environmental impact of transport links, tourist constructions or new energy production facilities must also be considered. Transport policy has been given a new direction: achieving a 'sustainable through flexibility' system, which means organizing transport in such a way as to optimize energy consumption. The development of the national transmission system shall be carried out in accordance with the requirements of conservation and environmental protection and the rational use of energy. The protection of human life and the environment is a priority in all transport-related relations.